The roles of the cytoskeleton in fungal tip growth: Insights from Aspergillus nidulans - Oakley, Berl; Peñalva, Miguel A. (Fungal genetics and biology, 2025)
Hyphal tip growth, the primary growth form in fungi, has not yielded its secrets easily or completely, but decades of research in many labs have greatly clarified this fascinating process. In this review, we will summarize progress that has been made in understanding the multiple roles microtubule and microfilament cytoskeletal networks play in tip growth. We will give particular attention to work in Aspergillus nidulans in which these subjects have been studied most intensely, but we will include findings obtained with other organisms where appropriate. Microtubules play a critical role in long range vesicular transport which is powered by the plus end-directed kinesin motor molecules KinA (a type 1 kinesin) and UncA (a type 3 kinesin). The minus end directed motor, dynein, plays an important role in moving kinesins and other cargos away from the hyphal apex so that they can be reused. Actin microfilaments and the motor molecule myosin V play an equally important role, and we will discuss the mechanisms by which microtubule- and actin-dependent transport cooperate to sustain rapid tip growth. With several motors operating in the same cytoplasm, adapter molecules are required to provide the mechanisms by which motors discriminate among cargos. These adapters are being identified and the critical roles of small GTPases are becoming increasingly clear. Endocytosis and exocytosis at the hyphal apex are absolutely required for tip growth and many of the key molecules in these processes have now been identified and their roles clarified. Myosin V is critical for concentrating vesicles carrying vesicular SNAREs at the Spitzenkörper. They then fuse with the apical membrane driven by interaction of vesicular (R-)SNAREs with target (Q-)SNAREs. Localization of the small GTPase RAB11 to the apex is likely a critical marker for the site of exocytosis. Actin patches are the major site of endocytosis, forming a collar near the apex in rapidly growing tip cells, and important progress has been made in understanding the roles of components of actin patches. In total, the machinery for delivering vesicles to the cell apex, the exocytosis machinery and the endocytosis machinery collectively interact to form a tip growth apparatus. Although we celebrate the progress that has been made, we will also point out some of the important remaining questions in this field. •Microtubules and actin cooperate to maintain hyphal tip growth by apical extension.•Myosin V and kinesin-1 transport secretory vesicles fueling tip growth to the apical dome, and their simultaneous ablation is lethal.•RAB GTPases and their effectors serve as adaptors between vesicles and motors.•Endocytosis is essential for hyphal tip growth and morphogenesis.•Actin patches concentrate in a subapical collar that facilitates polarization of cargo by endocytic recycling.